Abate halal com e sem insensibilização em ovinos: implicações sobre bem-estar animal e a eficiência de sangria - Sterza, Alessandra (2019)
The purpose of Stunting is to make animals unconscious so that they do not suffer pain or agony during bleeding. Knowing that there are differences in the slaughter, mainly related to the maintenance of religious traditions, it is necessary to evaluate the effects of these different types of slaughter. The aim of this study was to evaluate the implications on animal welfare and bleeding efficiency in halal slaughter with and without sheep numbness. We evaluated 102 commercial slaughtered sheep randomly separated by weight in two groups: insensitized (IC) and non-insensitized (SI). Animals without numbness showed signs of straightening and vocalization after 20 seconds of sticking. There was a significant difference for red blood cells (p <0.01), hemoglobin (p <0.01), total leukocytes (p <0.001), as well as stress biomarkers such as CK (p <0.01) and lactate (p <0.001). Although not statistically significant, LDH and cortisol were above baseline in both groups. No serum changes were observed for glucose and AST. There was a statistically significant difference for bleeding efficiency (p <0.01), with higher values for the group without numbness. The results showed that there was stress in halal slaughter with and without numbing and better bleeding efficiency in non-numbed animals.